Behaviorism Theory and Its Implications for Learning - Miftahul Ulum; Ahmad Fauzi (Yayasan Insan Mulia Bima, 2023)
Behaviorism is a learning theory that emphasizes behavior as the most appropriate object to research. Behavior is considered a more suitable object of research than thoughts or emotions. This article aims to describe behaviorist theory from it’s figures, then explain it’s implications for learning. This research is a literature review research that uses deductive and inductive analysis. The conclusion of this paper is that behaviorism theory has a significant contribution to learning. Behaviorism theory emphasizes the importance of forming desired behavior through reinforcement and eliminating undesirable behavior through punishment. In a learning context, this approach can help teachers shape and strengthen desired behavior.